PERGELARAN WAYANG KRUCIL SELOPURO STRUKTUR KUASA ISLAM JAWA DALAM RITUAL NYADRAN - rudi irawanto (Jurnal Budaya Nusantara, 2018)
Nyadran is an annual event in the village of Selopuro, Pitu District, Ngawi Regency, East Java. This event was held on every 10th Besar or 10 Dzulhijah which contained the salvation and performance of the krucil puppet. Activities in Nyadran and the performance of wayang krucil indicate the process of acculturation between authentic beliefs and Islamic spirituality. The acculturative process appears in the conscious prayer read out by the puppeteer and also in the puppet performance ritual. Prayers delivered at the slametan ritual and at the pre show influence the concept of pantheism, or the concept of manunggaling kawulo gusti. The concept of manuggaling kawulo gusti is one of the core of Javanese Islamic teachings.